MOF-Derived Cu3P nanoparticles coated with N-doped carbon for nitrogen fixation. Issue 16 (2nd February 2022) - Li, Jian; Lu, Xiaoying; Huang, Junfeng; Guo, Kailu; Xu, Cailing
Abstract : Cu3 P@NC electrocatalysts with a high electrochemical surface area and abundant defects exhibit a excellent ammonia yield rate and faradaic efficiency for the nitrogen reduction reaction. Abstract : Electrochemical nitrogen reduction is a significant alternative route for synthesizing ammonia, but constructing efficient catalysts for electrochemical nitrogen fixation still faces tough challenges. In this work, Cu3 P@NC (NC: nitrogen-doped carbon) nanosheets were prepared via the low-temperature pyrolysis–phosphating of Cu-MOFs. When applied to the nitrogen reduction reaction, Cu3 P@NC exhibited a high ammonia yield rate of 10.4 μg h −1 mg −1 cat at −0.3 V ( vs. RHE) and a faradaic efficiency (FE) of 6.3% at −0.1 V ( vs. RHE). The outstanding performance was attributed to the large electrochemical surface area and the defects induced as a result of N doping, which helped enhance N2 adsorption. This work provides a novel strategy for preparing N-doped carbon materials for wide-ranging applications.